The Centrality of Brand Awareness - Michael Adiwijaya; Erin McGuinness; John C Cary; Halimin Herjanto (Petra International Journal of Business Studies, 2021)
The brand concept, especially brand loyalty, has evolved significantly; however, this phenomenon is still considered far from complete. This study extends a long line of scholars’ efforts by investigating a moderating effect of brand awareness in triangle relationships between product innovation and brand trust and brand loyalty. The hypotheses were tested based on online questionnaire data collected from 100 Indonesian respondents. The Ordinary least square (OLS) regression analysis shows that brand awareness positively and significantly moderates these triangle relationships. Additionally, the direct relationships between product innovation on brand awareness and brand loyalty and brand trust and brand loyalty were found to be significant. This research offers future research direction and implications for business practitioners and academics.